Oxidant/antioxidant balance in patients with thyroid cancer - Akinci,Melih (2008)
PURPOSE: To compare the antioxidant enzyme activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and the levels of lipid peroxidation product malondialdehyde (MDA) in blood samples of thyroid cancer patients compared to healthy controls. METHODS: 43 control subjects (mean age 44±13 years) and 43 patients (43±13 years) presented with multinodular goiter whose fine needle aspiration revealed malignant cytology were included into this study. The SOD, MDA and GSH-Px activities were measured in control subjects, and before/20 days after thyroidectomy in thyroid cancer patients. RESULTS: SOD activities of pre-thyroidectomy, post-thyroidectomy and control groups were not different (p>0.05). Before thyroidectomy GSH-Px activities were lower (p<0.05) and MDA levels were higher (p<0.05) than the control group. In post- thyroidectomy, GSH-Px activity (p<0.05) increased, and MDA levels (p<0.05) decreased compared to prethyroidectomy levels. After thyroidectomy GSH-Px activity was significantly higher than the control group (p<0.05). Although post-thyroidectomy MDA levels significantly decreased, they were still higher than the control group (p<0.05). CONCLUSION: The superoxide dismutase does not seem to change with thyroid cancer and thyroidectomy but both antioxidant glutathione peroxidase and lipid peroxidation product malondialdehyde do. These preliminary findings may point out oxidant/antioxidant imbalance associated with thyroid cancer.